Dreamweaver MX 2004 - Crumlish, Christian (Sybex, 2011)
Dreamweaver MX 2004 Savvy is an incredibly in-depth and thorough guide to Macromedia's powerful web publishing software. This book includes detailed coverage of everything from migrating sites over from other applications to using Cascading Style Sheets to working with the five major server technologies to supporting e-commerce and blogs.